Sikap Ambivalensi Pribumi Dan Hibriditas Masyarakat Di Kepulauan Utara Jepang Dalam Film Animasi Joppani No Shima Karya Shigemichi Sugita - Hendrike Priventa (KIRYOKU, 2019)
This study aims to describe the indigenous ambivalence in the Joppani no Shima animated film and community hybridity in the Japanese Northern Islands in the animated film Joppani no Shima. The approach used is postcolonial with the perspective of Homi. K Bhaba. The results of this study are 1) The attitude of indigenous ambivalence in the film Joppani no Shima is divided into two, namely the attitude of loving the homeland and the attitude of looking at the colonizers higher. The attitude of indigenous ambivalence is one of the drivers of hybridity. 2) The hybridity of the North Island Islands of Japan can be seen in three aspects, namely the outlook on life, knowledge and lifestyle.Keywords : Animated film; North Japanese islands; postcolonial; ambivalence; hybridity